3D nickel foams with controlled morphologies for hydrogen evolution reaction in highly alkaline media. (15th January 2019) - Siwek, K.I.; Eugénio, S.; Santos, D.M.F.; Silva, M.T.; Montemor, M.F.
Abstract: Water electrolysis is the cleanest method for hydrogen production, and can be 100% green when renewable energy is used as electricity source. When the hydrogen evolution reaction (HER) is carried out in alkaline media, nickel (Ni) is a low cost catalyst and an interesting alternative to platinum. Still, its performance has to be enhanced to meet the high efficiency of the nobler metals, an objective that requires further tailoring of the surface area and morphology of Ni-based electrode materials. Unlike commercially available porous Ni, these features can be easily controlled via electrodeposition, a one-step process, taking advantage of the dynamic hydrogen bubble template (DHBT). Generally, changes in surface porosity and morphology have been mainly achieved by altering the main parameters, such as the current density or the deposition time. However, very scarce work has been done on the role of supporting electrolyte (i.e., its concentration and composition) in tailoring the foam features and consequently their catalytic activity. Hence, this approach paves the way to optimum design of metallic foam structures that can be obtained only with modifications in the electrolytic bath. In this work, 3D Ni foams are obtained from different composition baths by galvanostatic electrodeposition in the hydrogen evolution regime on stainless steel current collectors. Their porosity and morphology are analysed by optical microscopy and SEM. The electrochemical performance is evaluated by cyclic voltammetry, while catalytic activity towards HER and materials' stability in 8 M KOH are tested using polarisation curves and chronoamperometry measurements, respectively. The recorded high currents and extended stability of the Ni foams with dendritic morphology demonstrate its outstanding performance, making it an attractive cathode material for HER in highly alkaline media. Graphical abstract: Highlights: Electrolyte composition and concentration can tailor 3D Ni foam morphology. Dendritic and rough structures improve electrochemical utilisation of material. Presence of highly porous structure (pores) influences Tafel slope. High pore density with dendritic morphology are desirable electrocatalyst properties.